Effect of Bacillus coagulans BC99 supplementation on body weight and gut microbiota in overweight and obese individual: a randomized, double-blind, placebo-controlled study - Wang, Rui; Zhang, Guoming; Wang, Xiaoya; Xing, Zefeng; Li, Zhen; Li, Lixiang (Frontiers in Nutrition, 2025)
IntroductionProbiotic supplementation is a safe and effective way to reduce overweight and obesity by regulating the gut microbiota. The Bacillus coagulans strain BC99 is derived from humans and has various probiotic-related, acid resistance, bile salt resistance, and adhesion-related domains in the genome. This study aimed to assess the effects of BC99 on the gut microbiota, body weight and lipid profiles of overweight and obese individuals.MethodsA total of 66 adult individuals were randomly assigned to a probiotic group (supplemented with 5 × 109 colony-forming units of BC99 per day along with 3 g of maltodextrin) and placebo group (supplemented with 3 g of maltodextrin daily) in a 1:1 ratio.ResultsAfter 8 weeks of oral administration, BC99 intervention significantly decreased the body weight of overweight individual (P < 0.01). Weight loss was significantly greater in the probiotic group than in the placebo group (P < 0.05). No significant differences were observed in lipid profiles between two groups. The microbiota analysis revealed that BC99 intervention significantly improved the β-diversity at week 4. The genus Parabacteroides was negatively correlated with body weight and was found to be enriched in the BC99 group.DiscussionThese findings suggest that B. coagulans strain BC99 could be a beneficial candidate for modulating the gut microbiota and improve body weight management for overweight individuals.Clinical trial registrationClinicalTrials.gov, identifier NCT06077383.